Oridonin suppresses autophagy and survival in rheumatoid arthritis fibroblast-like synoviocytes - Shou-Di He; Sheng-Guang Huang; Hui-Jun Zhu; Xiao-Guang Luo; Kang-Han Liao; Jie-Yao Zhang; Ning Tan; De-Yu Li (Taylor & Francis Group, 2020)
Context Oridonin exhibits various pharmacological and physiological activities, including antioxidant, antibacterial, anti-inflammatory, pro-apoptotic, anticancer and neurological effects. However, its role in rheumatoid arthritis (RA) is yet to be revealed. Objective We evaluated the effects of oridonin on the survival and autophagy of RA-fibroblast-like synoviocytes (FLSs). Materials and methods RA-FLSs were treated with oridonin at serial concentrations of 0, 2, 4, 6, 8 and 10 µg/mL for 24, 48 and 72 h. Then, cell proliferation and apoptosis were measured. A GFP-LC3 plasmid was transfected into the cells to determine autophagy. Results Oridonin suppressed RA-FLS proliferation in a dose-dependent manner. The half maximal inhibitory concentrations (IC50) of oridonin at 24, 48 and 72 h were 8.28, 7.88 and 8.35 µg/mL, respectively. Treatment with oridonin for 24 h increased apoptosis by 4.1%, and increased the protein levels of Bax and cleaved caspase-3 but significantly decreased the levels of IL-1β in the culture supernatant (p < 0.05). In addition, 6 h of oridonin treatment significantly decreased the number of GFP-LC3 punctate dots and inhibited the protein levels of ATG5 and Beclin1 by 80.01% and 42.12%, respectively. Chloroquine (CQ) significantly reinforced the effects of oridonin on inhibition of autophagy, suppression of proliferation, and induction of apoptosis in RA-FLSs (p < 0.05). Conclusions Our results indicate that treatment with oridonin in combination with CQ inhibits autophagy and cell proliferation and induces apoptosis in RA-FLSs more effectively than treatment oridonin alone. This finding indicates that oridonin is a potential therapeutic agent for RA.